Efficient Modeling of Heat Conduction across Thin Surface Coatings on 3D Anisotropic Substrate - Shiah, Yui-Chuin; Hwang, Po-Wen; Hematiyan, Mohammad-Rahim; Tuan, Nguyen (Aerospace, 2022)
In aerospace applications, surface coatings have been widely applied for variouspurposes. One typical example is the use of thermal barrier coating (TBC) applied on anisotropic substrate for enhancing the heat resistance of the substrate under severe operational environments. Numerical modeling of thin coatings usually present difficulties for most techniques, due to their dimensional orders being far below that of the substrate. This paper presents a numerical methodology to efficiently model the heat conduction across thin layered coatings on 3D, generally anisotropic, media by the boundary element method (BEM). In the modeling, singularities of the surface-integrals are weakened by using Green’s Second Identity, where a newly introduced function is solved by the finite volume method. Using the proposed approach, the heat conduction problem can be efficiently analyzed, despite the great difference in dimensional orders in comparison with that of the substrate beneath, by simply employing very coarse surface meshes. Such analysis shows great efficiency in calculating the nearly singular boundary integrals for the modeling. Finally, two benchmark examples of thermal barrier coatings are analyzed to illustrate the effectiveness of this approach.